A clinical study on lateral pancreaticojejunostomy in a case of chronic pancreatitis - Manapure, Suhas B.; Munde, Anil S.; Kasale, Ravibhushan J.; Lokare, Pramod (International Surgery Journal, 2021)
Lateral pancreaticojejunostomy is a seldom performed procedure in a peripheral tertiary health care centre. Very few numbers of cases are reported that undergoes surgical procedures for chronic pancreatitis. We report a such rare case in our institute that undergone pancreatic drainage procedure. A 70 year old poor patient was admitted in our institute with a complaint of chronic abdominal pain, subsequently diagnosed to be having chronic pancreatitis with complications with pancreatic duct calculus. Pancreatic drainage procedure, lateral pancreaticojejunostomy was performed and we analysed for the outcome of the procedure with regards to pain relief, anastomotic leak, quality of life and return to work. Patient recovered well post-operatively, reported pain relief, suffered no anastomotic leak and experienced improved quality of life. Lateral pancreaticojejunostomy provides excellent surgical choice for patients of chronic pancreatitis with pancreatic duct calculus with acceptable rates of pain relief, morbidity and mortality, without worsening pancreatic insufficiency.